Isolation of curcumin from Curcuma longa Linne (Fam. Zingiberaceae) - Sayson, Fely Rose A.; Castillo, Amorita V. (Quezon City: College of Pharmacy, University of the Philippines, 1978.)
Curcumin, the coloring matter of Curcuma longa Linne (Fam. Zingiberaceae), is extracted from the powdered airdried roots and rhizomes.
Thin layer chromatography of the benzene extract on silica gel plates with benzene-ethyl acetate (21:9) gives 5 zones. Corresponding Rf values lead to the identification of the constituents present.
Spectrophotometric analysis of the isolated crystals gave peaks with values of 265 nm and 200 nm respectively.
​Thesis (Bachelor of Science in Pharmacy)--University of the Philippines, March 1979.
Keywords: Turmeric